The Influence of Heat and Surface Treatment on the Functional Properties of Ti6Al4V Alloy Samples Obtained by Additive Technology for Applications in Personalized Implantology - Anita Kajzer; Gabriela Wielgus; Krystian Drobina; Aleksandra Żurawska; Wojciech Kajzer (Applied Sciences)
The main aim of this study was to evaluate the influence of heat and surface treatment on the physicochemical properties of samples produced using Direct Metal Sintering incremental technology from Ti64ELI titanium powder. Two groups of samples were selected for the study: sandblasted and mechanically polished samples. Each group consisted of samples in the initial state and after heat treatment carried out at temperatures of 800 °C, 910 °C, and 1020 °C. The article presents the results of microscopic metallographic observations, wettability and surface topography, hardness, and resistance to pitting corrosion in Ringer’s solution, together with microscopic evaluation of the surfaces before and after testing. Based on the test results, both heat and surface treatments were found to alter the functional properties of the printed samples. All the tested samples show hydrophilic properties. Heat treatment at 1020 °C produces the best resistance to pitting corrosion. This information is important when selecting the mechanical properties of the biomaterial and the physicochemical properties of the surface for a specific type of stabilizer. The choice of appropriate heat treatment and surface treatment of the implant will also depend on the length of time the implant remains in the body.